Agricultural Communicators in Education - Jim Shaner; Don Esslinger (Journal of Applied Communications, 1982)
Editorial back matter for vol.64, no.4, Jan-Mar (1981) of The ACE Quarterly, Official Journal of the Agricultural Communicators in Education